Productive Waqf Development Strategy to Grow Community Economy in Selangor Malaysia - Lukman Yafi (Walidem Institute and Publishing (WIP), 2024)
This research aims to investigate productive waqf development strategies to improve the community economy in Selangor, Malaysia. The research method used is descriptive and quantitative analysis, using primary and secondary data collected through surveys, interviews and literature studies. The research results show that implementing the productive waqf development strategy has positively contributed to the people's economy in Selangor. Increasing production and utilization of waqf assets has provided new business opportunities and increased income for local communities. The productive waqf development strategy also provides significant social benefits, such as increasing welfare and community empowerment. This research provides valuable insights for the government and other stakeholders in designing policies and programs to strengthen the role of waqf in local economic development in Selangor, Malaysia.